Advertising in Competitive Markets - Stegeman, Mark (American Economic Review, 1991)
In this paper, small firms sell a homogeneous good to small consumers under conditions of free entry, but consumers receive price information only through firms' advertising. In equilibrium, every firm on the continuous price distribution buys less advertising than is socially optimal. The result is robust if firms advertise in just one medium. If readers of different advertising media are positively correlated, excess advertising can occur in media used exclusively to advertise discount prices. Copyright 1991 by American Economic Association.